Effect of Work Experience and Work Placement on Employee Performance in Companies PT. Hadji Kalla at Makassar - Hasyim, Hasyim (Patria Artha University, 2018)
This study aims to determine and analyze the influence of work experience on employee performance in the company PT. Hadji Kalla in Makassar and to find out and analyze the influence of work placements on employee performance at PT. Hadji Kalla in Makassar. The analytical method used in this study is the Multiple Regression analysis method. Research data was obtained from employees of PT. Hadji Kalla in Makassar. The research approach is an explanatory causal approach.The results show that work experience has a direct influence on employee performance. Work experience possessed by employees will be able to help employees in carrying out their duties so as to improve employee performance, and work placements have a positive and significant effect on employee performance in the company PT. Hadji Kalla in Makassar, meaning that employee performance can increase if influenced by employee work placements